On measuring selective attention to an expected sensory modality. - Spence, C; Driver, J (1997)
Perceptual judgments can be affected by expectancies regarding the likely target modality. This has been taken as evidence for selective attention to particular modalities, but alternative accounts remain possible in terms of response priming, criterion shifts, stimulus repetition, and spatial confounds. We examined whether attention to a sensory modality would still be apparent when these alternatives were ruled out. Subjects made a speeded detection response (Experiment 1), an intensity or color discrimination (Experiment 2), or a spatial discrimination response (Experiments 3 and 4) for auditory and visual targets presented in a random sequence. On each trial, a symbolic visual cue predicted the likely target modality. Responses were always more rapid and accurate for targets presented in the expected versus unexpected modality, implying that people can indeed selectively attend to the auditory or visual modalities. When subjects were cued to both the probable modality of a target and its likely spatial location (Experiment 4), separable modality-cuing and spatial-cuing effects were observed. These studies introduce appropriate methods for distinguishing attention to a modality from the confounding factors that have plagued previous normal and clinical research.